Improvement of soil acidification in tea plantations by long-term use of organic fertilizers and its effect on tea yield and quality - Ye, Jianghua; Wang, Yuhua; Wang, Yuchao; Hong, Lei; Jia, Xiaoli; Kang, Jiaqian; Lin, Shaoxiong; Wu, Zeyan; Wang, Haibin (Frontiers in Plant Science, 2022)
In this study, different fertilizers were used to treat the acidified tea plantation soils for 4 consecutive years to analyze the remediation effect of different fertilizers on acidified soil and their effects on tea yield and quality. The results showed that during the period of 2017-2021, the soil pH value of tea plantation (S1) with long-term use of chemical fertilizer decreased continuously, from 3.07 to 2.82. In the tea plantation (S2), the soil pH value was stable between 4.26 and 4.65 in the combination of organic fertilizer and chemical fertilizer for a long time. The tea plantation (S3) with long-term use of organic fertilizer has a stable soil pH value between 5.13 and 5.33, which is most suitable for the growth of tea trees. The analysis results of tea yield and quality indicators (tea polyphenols, theanine, amino acids, caffeine, catechin components) showed that after long-term use of chemical fertilizer in S1 tea plantation, soil pH value decreased continuously, soil acidification intensified, tea tree growth was hindered, and tea yield and quality decreased continuously. S2 tea plantation used some organic fertilizer in combination with chemical fertilizer for a long time, the soil pH value gradually improved, soil acidification weakened, and tea yield and quality improved steadily. After long-term use of organic fertilizer in S3 tea plantation, soil acidification was significantly improved, which was conducive to the normal growth of tea trees and the yield and quality of tea reached the maximum. The results of interaction analysis showed that the long-term use of chemical fertilizer had a negative effect on the growth of tea trees, and the combination of organic fertilizer and chemical fertilizer improved the growth of tea trees to some extent, but the effect was poor, while the long-term use of organic fertilizer was the most beneficial to the growth of tea trees and most conducive to ensuring the yield and quality of tea. This study provides important practical significance for the remediation and fertilizer regulation of acidified tea plantation soils.